Understanding the status quo of Sino-US trade friction - Chen, Ge; Zeng, Huan Zhang (International Journal of Psychosocial Rehabilitation, 2020)
Abstract--- China’s statistics on exports to the United States exclude goods sold to Hong Kong or to a third country that is reexported to the United States, while U.S. statistics include such reexports as being from China. These variations in statistical methods have naturally led to divergent statistical results. An example of such statistical divergence can be seen in the trade surplus of $21 billion recorded by Chinese Customs in 1998, while that recorded by U.S. Customs was $57 billion. In addition, U.S. Customs calculations of imports from China ignore the value-added from processing and repackaging of Chinese products in Hong Kong and in third countries for the purpose of re-export. Therefore, from the Chinese viewpoint, U.S. imports from China are overestimated.